Derivatives and corporate risk management: participation and volume decisions in the insurance industry - J. David Cummins; Richard D. Phillips; Stephen D. Smith (Federal Reserve Bank of Atlanta, 1997)
In this paper we formulate and test a number of hypotheses regarding insurer participation and volume decisions in derivatives markets. Several specific hypotheses are supported by our analysis. We find evidence consistent with the idea that insurers are motivated to use financial derivatives to hedge the costs of financial distress, interest rate, liquidity, and exchange rate risks. We also find some evidence that insurers use these instruments to hedge embedded options and manage their tax bills. We also find evidence of significant economies of scale in the use of derivatives. Interestingly, we often find that the predetermined variables we employ display opposite signs in the participation and volume regressions. We argue that this result is broadly consistent with the hypothesis that there is also a per unit premium associated with hedging and that, conditional on having risk exposures large enough to warrant participation, firms with a larger appetite for risk will be less willing than average to pay this marginal cost.
Keywords: 330; Corporations - Finance; Derivative securities; Financial services industry; Business enterprises